Pengaruh Orientasi Kewirausahaan terhadap Kinerja Pemasaran Digital melalui Jejaring Usaha dan Orientasi Pasar sebagai Variabel Intervening pada UMKM - Abdi Ramdan; Resita Septia Rahma; Siti Sofiyah; Yanto Heryanto (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the effect of entrepreneurial orientation on the digital marketing performance of Micro, Small, and Medium Enterprises (MSMEs), by considering the roles of business networking and market orientation as intervening variables. The research is motivated by the importance of MSMEs adapting to the dynamics of digital marketing in the era of technology-driven economic transformation. A quantitative method with a survey approach was employed, involving 70 respondents from the food and beverage sector who are members of ASIPA in Serang Regency, Banten. The analysis technique used was Structural Equation Modeling (SEM) with the assistance of SmartPLS software.The results show that entrepreneurial orientation does not have a significant direct effect on digital marketing performance, although the direction of the influence is positive. However, entrepreneurial orientation has a positive and significant effect on both business networking and market orientation. Furthermore, both business networking and market orientation were found to have a positive and significant effect on digital marketing performance. These findings indicate that business networking and market orientation serve as intervening variables that strengthen the relationship between entrepreneurial orientation and digital marketing performance. This study offers important implications for MSME actors and policymakers in enhancing MSME competitiveness